Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Retraction Note: Patterns of niche filling and expansion across the invaded ranges of Halyomorpha halys in North America and Europe - Gengping Zhu; Tara D. Gariepy; Tim Haye; Wenjun Bu (Journal of Pest Science, 2025)

Does intraspecific variation in Trissolcus japonicus affect its response to non-target hosts? - Nina Häner; Fleur Fenijn; Tim Haye (BioControl, 2024)
Host specificity is a key criterion for the implementation of any biological control program. In parasitoid wasps, host specificity is mediated by their response to chemical cues directly and indirectly associated with their hosts during foraging. Although intraspecific variation in foraging behaviour is documented, it is rarely integrated into risk assessment studies of potential biological control agents, as is the case for Trissolcus japonicus (Ashmead) (Hymenoptera: Scelionidae), an Asian egg parasitoid and biological control agent of the invasive Halyomorpha halys (Stål) (Hemiptera: Pentatomidae). In the present study, we compared the behavioural response of T. japonicus females of an adventive line present in Switzerland and an Asian line (Beijing USDA), recently mass released in Italy, to cues of its target host H. halys and non-target host Pentatoma rufipes (L.) (Hemiptera: Pentatomidae). We observed minimal differences in host acceptance, exploitation and suitability in no-choice tests. In contrast, the behavioural response to host contact kairomones left on leaf substrates significantly differed between the two lines. While both lines preferred chemical footprints of H. halys in comparison to P. rufipes , females of the Beijing USDA line responded more strongly to host kairomones. The observed intraspecific variation in behavioural traits highlights the relevance of considering genetically distinct parasitoid lines and their host foraging behaviour in biological risk assessment studies. However, the implications of intraspecific variation in parasitoid foraging behaviour for biological control of a pest and non-target effects in the field remain challenging to predict.

Biology, impact, management and potential distribution of Aromia bungii, a major threat to fruit crops around the world - Kiran Jonathan Horrocks; Jinping Zhang; Tim Haye; M. Lukas Seehausen; Ramona Maggini; Xiaoqing Xian; Juhong Chen; Francesco Nugnes; Jana Collatz; Angela Gruber; Tara D. Gariepy (Journal of Pest Science, 2024)
Aromia bungii Faldermann (Coleoptera: Cerambycidae) is an emerging invasive pest of economically important Prunus species that is native to China, Mongolia, the Russian Far East, Korea, and Vietnam. It was recently introduced to Japan, Germany, and Italy, where it is spreading and damaging crops and ornamental trees. It exhibits an adaptable lifecycle, a high reproductive output, and the larvae live concealed under the bark of infested trees, which are traits that promote its invasiveness. Detection and monitoring of A. bungii currently rely upon visual identification of infested trees that are usually already damaged, which is inefficient and not target-specific. Current control methods rely primarily upon the labour-intensive physical removal of infested trees. Although native parasitoid natural enemies of A. bungii provide control in Chinese orchards, none are appropriate for classical biological control in invaded areas due to biosafety concerns surrounding their broad host ranges. However, entomopathogenic fungi and nematodes may provide viable options for biological control in invaded ranges. Recent advancements in semiochemical baited traps may provide sustainable, target-specific, and efficacious methods to monitor and control A. bungii . There remains much to learn about the biology and control of A. bungii , and continued advancements in the study of sustainable control tools are needed for the management of this emerging pest.

Does the fundamental host range of Trissolcus japonicus match its realized host range in Europe? - Tim Haye; Silvia T. Moraglio; Francesco Tortorici; Cristina Marazzi; Tara D. Gariepy; Luciana Tavella (Journal of Pest Science, 2024)
Unintentional introduction of natural enemies has increased in recent years due to a massive rise in global trade and tourism. One such natural enemy is the Asian egg parasitoid Trissolcus japonicus , a promising agent for classical biological control of Halyomorpha halys. In Europe, adventive T. japonicus populations have been detected in Switzerland, Italy and Germany. Host specificity testing demonstrated that its fundamental host range is fairly broad; however, it is unclear whether spatial or temporal refuges reduce parasitism of non-target species in the field. To address this, the realized host range of T. japonicus was assessed over three years by exposing sentinel egg masses of H. halys and 18 non-target species and collecting naturally laid egg masses in Switzerland and Italy. In total, 15 of 18 non-target species were successfully parasitized by T. japonicus in the field, confirming its broad fundamental host range. However, most non-target species were less parasitized by T. japonicus than H. halys , profiting from either partial temporal or spatial refuges from parasitism. Species with an unusual life cycle and the same ecological niche as H. halys , such as Pentatoma rufipes , which was the most parasitized non-target species in both countries, potentially face an increased risk of parasitism. In contrast, beneficial non-target effects may occur for the invasive pest, Nezara viridula , which suffered high non-reproductive mortality induced by T. japonicus . In both cases, life table studies will be needed to determine the impact of non-target parasitism and the potential consequences at the population level.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The genetics of vigour-related traits in chickpea (Cicer arietinum L.): insights from genomic data - Duong T. Nguyen; Julie E. Hayes; Judith Atieno; Yongle Li; Ute Baumann; Angela Pattison; Helen Bramley; Kristy Hobson; Manish Roorkiwal; Rajeev K. Varshney; Timothy D. Colmer; Tim Sutton (Theoretical and Applied Genetics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Current distribution and voltinism of the brown marmorated stink bug, Halyomorpha halys, in Switzerland and its response to climate change using a high-resolution CLIMEX model - Sibylle Stoeckli; Raphael Felber; Tim Haye (International Journal of Biometeorology, 2020)
Climate change can alter the habitat suitability of invasive species and promote their establishment. The highly polyphagous brown marmorated stinkbug, Halyomorpha halys Stål (Hemiptera: Pentatomidae), is native to East Asia and invasive in Europe and North America, damaging a wide variety of fruit and vegetable crops. In Switzerland, crop damage and increasing populations have been observed since 2017 and related to increasing temperatures. We studied the climatic suitability, population growth, and the number of generations under present and future climate conditions for H. halys in Switzerland, using a modified version of the bioclimatic model package CLIMEX. To address the high topographic variability in Switzerland, model simulations were based on climate data of high spatial resolution (approx. 2 km), which significantly increased their explanatory power, and identified many more climatically suitable areas in comparison to previous models. The validation of the CLIMEX model using observational records collected in a citizen science initiative between 2004 and 2019 revealed that more than 15 years after its accidental introduction, H. halys has colonised nearly all bioclimatic suitable areas in Switzerland and there is limited potential for range expansion into new areas under present climate conditions. Simulations with climate change scenarios suggest an extensive range expansion into higher altitudes, an increase in generations per year, an earlier start of H. halys activity in spring and a prolonged period for nymphs to complete development in autumn. A permanent shift from one to two generations per year and the associated population growth of H. halys may result in increasing crop damages in Switzerland. These results highlight the need for monitoring the spread and population development in the north-western part of Switzerland and higher altitudes of the valleys of the south.

Fundamental host range of Trissolcus japonicus in Europe - Tim Haye; Silvia T. Moraglio; Judith Stahl; Sara Visentin; Tommaso Gregorio; Luciana Tavella (Journal of Pest Science, 2020)

First discovery of adventive populations of Trissolcus japonicus in Europe - Judith Stahl; Francesco Tortorici; Marianna Pontini; Marie-Claude Bon; Kim Hoelmer; Cristina Marazzi; Luciana Tavella; Tim Haye (Journal of Pest Science, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Host specificity of Asian parasitoids for potential classical biological control of Drosophila suzukii - Pierre Girod; Océane Lierhmann; Teddy Urvois; Ted C. J. Turlings; Marc Kenis; Tim Haye (Journal of Pest Science, 2018)

Using the egg parasitoid Anastatus bifasciatus against the invasive brown marmorated stink bug in Europe: can non-target effects be ruled out? - Judith M. Stahl; Dirk Babendreier; Tim Haye (Journal of Pest Science, 2018)

Special issue on the brown marmorated stink bug, Halyomorpha halys: an emerging pest of global concern - Tim Haye; Donald C. Weber (Journal of Pest Science, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

The potential global distribution of the brown marmorated stink bug, Halyomorpha halys, a critical threat to plant biosecurity - Darren J. Kriticos; John M. Kean; Craig B. Phillips; Senait D. Senay; Hernando Acosta; Tim Haye (Journal of Pest Science, 2017)

Seasonal parasitism and host specificity of Trissolcus japonicus in northern China - Jinping Zhang; Feng Zhang; Tara Gariepy; Peter Mason; Dave Gillespie; Elijah Talamas; Tim Haye (Journal of Pest Science, 2017)

Native egg parasitoids recorded from the invasive Halyomorpha halys successfully exploit volatiles emitted by the plant–herbivore complex - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Maria Cristina Foti; Ezio Peri; Lara Maistrello; Tim Haye; Eric Conti (Journal of Pest Science, 2017)

RETRACTED ARTICLE: Patterns of niche filling and expansion across the invaded ranges of Halyomorpha halys in North America and Europe - Gengping Zhu; Tara D. Gariepy; Tim Haye; Wenjun Bu (Journal of Pest Science, 2017)

Erratum to: Non-crop plants used as hosts by Drosophila suzukii in Europe - Marc Kenis; Lorenzo Tonina; René Eschen; Bart van der Sluis; Manuel Sancassani; Nicola Mori; Tim Haye; Herman Helsen (Journal of Pest Science, 2017)

Non-crop plants used as hosts by Drosophila suzukii in Europe - Marc Kenis; Lorenzo Tonina; René Eschen; Bart van der Sluis; Manuel Sancassani; Nicola Mori; Tim Haye; Herman Helsen (Journal of Pest Science, 2016)
The invasive spotted wing drosophila Drosophila suzukii , a fruit fly of Asian origin, is a major pest of a wide variety of berry and stone fruits in Europe. One of the characteristics of this fly is its wide host range. A better knowledge of its host range outside cultivated areas is essential to develop sustainable integrated pest management strategies. Field surveys were carried out during two years in Italy, the Netherlands and Switzerland. Fruits of 165 potential host plant species were collected, including mostly wild and ornamental plants. Over 24,000 D. suzukii adults emerged from 84 plant species belonging to 19 families, 38 of which being non-native. Forty-two plants were reported for the first time as hosts of D. suzukii . The highest infestations were found in fruits of the genera Cornus , Prunus , Rubus , Sambucus and Vaccinium as well as in Ficus carica, Frangula alnus, Phytolacca americana and Taxus baccata. Based on these data, management methods are suggested. Ornamental and hedge plants in the vicinity of fruit crops and orchards can be selected according to their susceptibility to D. suzukii . However, the widespread availability and abundance of non-crop hosts and the lack of efficient native parasitoids suggest the need for an area-wide control approach.

Range expansion of the invasive brown marmorated stinkbug, Halyomorpha halys: an increasing threat to field, fruit and vegetable crops worldwide - Tim Haye; Tara Gariepy; Kim Hoelmer; Jean-Pierre Rossi; Jean-Claude Streito; Xavier Tassus; Nicolas Desneux (Journal of Pest Science, 2015)

Characterization of ammonia gas release from concrete added with ammoniated fly ash - Lin Shou; Joshua Hayes; Weizhi Cheng; Chang-Yu Wu; Timothy Townsend; Tim Vinson; John Schert (Air Quality, Atmosphere & Health, 2014)

A participatory approach to the establishment of a baseline scenario for a reforestation Clean Development Mechanism project - Catherine Potvin; Petra Tschakert; Frédéric Lebel; Kate Kirby; Hector Barrios; Judith Bocariza; Jaime Caisamo; Leonel Caisamo; Charianito Cansari; Juan Casamá; Maribel Casamá; Laura Chamorra; et al. (Mitigation and Adaptation Strategies for Global Change, 2007)

Conservation of Coral Reefs after the 1998 Global Bleaching Event - Tom Goreau; Tim McClanahan; Ray Hayes; Al Strong (Conservation Biology, 2000)